Why the Construction Trades Have a Valuable Role in Meeting the Climate Challenge - Calvert, John (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2024)
The construction industry accounts for 18 per cent of Canada’s greenhouse gas emissions. There is extensive evidence that this can be reduced significantly by implementing aggressive net zero building practices. However, the way the industry is organized impedes this achievement because it fails to promote the development of a broadly based, highly qualified, climate-literate workforce. Successful low carbon construction requires enhancement of workers’ knowledge, skills, and competencies because it requires much higher energy performance standards than traditional construction practice. Yet the industry remains wedded to the current system of low-bid, low-quality construction to cut costs. The organization of much construction work reflects a Taylorist approach, with extensive piecework and subcontracting that relies heavily on precarious, unskilled, and semi-skilled workers. Most employers avoid investing in trades training, leaving it to governments, unions, and individual workers to fund workforce development. Committed to a deregulated market with minimal government interference in their profit-making activities, many contractors oppose tougher building and energy regulations while lobbying against higher labour standards, occupational certification requirements, and union organizing. To meet their net zero targets, governments must recognize that market forces are inadequate to create the well-trained, highly skilled workforce needed. Major policy interventions are required to force industry to make the necessary changes in vocational education and training (vet) and employment practices – changes designed to upskill the construction workforce and give workers and unions a greater voice in shaping climate-informed building practice.